Active Antimicrobial Food Packaging - Var, Işıl; Uzunlu, Sinan (IntechOpen, 2019)
Active antimicrobial food packaging is a new generation of packaging. Antimicrobial food additives are incorporated in the food packaging systems to inhibit, retard, or inactivate microbial growth to extend the shelf life of foods. This book is composed of five chapters, and is aimed at introducing the reader to active antimicrobial food packaging, as well as concerns of the consumers on synthetic-based food additives.